PELATIHAN IRIGASI TETES BERTINGKAT UNTUK TANAMAN HORTIKULTURA DI DESA JAGARAGA KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Negara, I Dewa Gede Jaya; Pradjoko, Eko; Pracoyo, Atas; Akmaludin, Akmaludin; Supriyadi, Anid; Saadi, Yusron; Suparjo, Suparjo; Yasa, I Wayan; Saidah, Humairo; Hasyim, Hasyim (Universitas Mataram, 2024)
The people of Poktan Beriuk Maju, Jagaraga Village, are mostly farmers who own land with varying amounts of land, and have a minimum of 2 acres of yard land and many of them are empty, so they need to be used for home farming to help provide food independently. The existence of water sources from springs around settlements and water from shallow wells can also be used to support agricultural activities in the residential area of ​​each potential house. Apart from that, by utilizing limited water sources, such as water from shallow wells and springs around housing, it is an opportunity for the community to farm vegetables and the like to help with the community's daily kitchen needs. This service aims to train people to make multilevel drip irrigation so that they can later be used as a farming method in their home gardens. Before being trained, residents need to be given knowledge about efficient drip irrigation so that participants gain sufficient knowledge about irrigation because its application is very different from traditional irrigation. The service was carried out in the initial stages of survey, the stage of strengthening efficient irrigation, the training stage of making multi-level drip irrigation networks using PVC pipes with emitters, the land was filled with polybags filled with soil as a planting medium. Activities consist of outreach on irrigation and drip irrigation as well as training. This service has succeeded in providing knowledge about irrigation and drip water efficient irrigation at the Beriuk Maju Poktan. It has succeeded in building a multi-level drip irrigation network and is ready for farming use, and can be continued by applying it to horticultural crops as a medium for learning about residential farming.